Residual platelet reactivity is an independent predictor of myocardial injury in acute myocardial infarction patients on antiaggregant therapy - Marcucci, Rossella; Paniccia, Rita; Antonucci, Emilia; Poli, Serena; Gori, Anna Maria; Valente, Serafina; Giglioli, Cristina; Lazzeri, Chiara; Prisco, Domenico; Abbate, Rosanna; Gensini, Gian Franco (Thrombosis and Haemostasis, 2007)
In this study we sought to evaluate if platelet function measured after percutaneous coronary intervention (PCI) affects the severity of myocardial infarction (MI), measured by markers of cardiac necrosis. We measured platelet function by both a point-of-care assay (PFA-100) and platelet-rich plasma aggregation by two agonists (arachidonic acid –AA- and 2 and 10 μM ADP) in 367 patients with MI after PCI (200 patients on dual antiplatelet agents – group A- and 167 on dual antiplatelet agents plus GpIIb/ IIIa inhibitors – group B). One hundred twenty-one (32.9%) patients were found to have a residual platelet reactivity (RPR) by PFA (CT/EPI <203 sec): 74/200 (37%) in group A and 47/167 (28.1%) in group B (p=0.07). In 129 (35.1%) patients we found a RPR by AA-PA: 80/200 (40%) in group A and 49/167 (29.3%) in group B (p<0.05). Seventeen out of 367 (4.6%) were found to have a RPR by ADP2-PA [15/200 (7.5%) in group A and 2/167 (1.2%) in group B; p<0.005] and 88/367 (23.9%) by ADP10-PA [64/200 (32%) in group A and 24/167 (14.4%) in group B, p<0.0001]. CK-MB and cTnI mean peak values were significantly higher in the first tertile of CT/ADP and CT/EPI distribution with respect to the other tertiles and they were significantly higher in patients with RPR by CT/EPI in both groupA and group B patients. CK-MB and cTnI peak values were significantly higher in the third tertile of AA-PA,ADP 2 μM-PA and ADP 10 μM-PA distribution with respect to the other tertiles and were significantly higher in patients with RPR by AA-PA and by ADP 10-PA in both group A and group B patients. Multivariate analysis revealed platelet function as an independent predictor of CK-MB and cTnI peak values in both groups of patients independently of clinical, laboratory ad procedural parameters. In conclusion, we found that the severity of MI in patients with MI undergoing primary PCI is influenced by a persistent platelet activation on multiple antiplatelet therapy.
Keywords: Aspirin resistance; clopidogrel resistance; post-treatment platelet reactivity; myonecrosis; myocardial infarction